2016
DOI: 10.1016/j.jascer.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of silica nanoparticles from clay

Abstract: We report a method to synthesize silica nanoparticles from bentonite clay. A series of thermal and acid treatment processes was performed on bentonite clay to lower the alumina and increase the silica content. The obtained silica rich clay was treated in two different concentrations (10 wt% and 40 wt%) with sodium hydroxide solution to form sodium silicate solutions (SSS). One type of SSS was hydrolyzed with three different concentrations (5 M, 10 M and 15 M) of nitric acid in the presence of ethanol as cosolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 27 publications
(27 reference statements)
4
49
0
Order By: Relevance
“…According to XRD spectra, the formation of polymer on the silica surface, plot the intensity of calculated counts versus position of 2θ° (Figure ). As can be seen, broad peaks of silica bands (22 ± 1°) suggest that the silica particles are at an amorphous state . The intensity of silica particles (SiO 2 ) at 22° is lower than the silica modified particles (TMSP‐SiO 2 ) due to the reduction of the size of the silica particles from microparticles to submicro particles .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…According to XRD spectra, the formation of polymer on the silica surface, plot the intensity of calculated counts versus position of 2θ° (Figure ). As can be seen, broad peaks of silica bands (22 ± 1°) suggest that the silica particles are at an amorphous state . The intensity of silica particles (SiO 2 ) at 22° is lower than the silica modified particles (TMSP‐SiO 2 ) due to the reduction of the size of the silica particles from microparticles to submicro particles .…”
Section: Resultsmentioning
confidence: 94%
“…As can be seen, broad peaks of silica bands (22 AE 1 ) suggest that the silica particles are at an amorphous state. 40 The intensity of silica particles (SiO 2 ) at 22 is lower than the silica modified particles (TMSP-SiO 2 ) due to the reduction of the size of the silica particles from microparticles to submicro particles. 40 After polymerization, the intensity at 22 was attributed to silica band for MIP, which was decreased when compared with the silica modified particles, suggesting the formation of the polymer.…”
Section: Optimization Of Polymer Layer Functionalities and Xrd Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore likely that increasing amounts of nickel will be produced from laterites. Since laterite type ores naturally occur close to the surface, economical open pit mining techniques are employed to recover the ore after removal of the overburden [3]. The laterite ore consists of fresh saprolite such as K 0.4 (Si 3.0 Al 1.0 ) 4.0 (Al 2.0 Mg 0.3 ) 2.33 O 10 (OH) 2 and nontronite such as Na 0,3 (Fe 3+ ) 2 (Si,Al) 4 O 10 (OH) 2 •nH 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Stopic et al [14] have shown the reaction path of direct forsterite carbonation in the aqueous solution without any deeper consideration of the formed silica particles as shown Equations (1)- (3) and Figure 1.…”
Section: Introductionmentioning
confidence: 99%